Efficacy and Safety of Laser Therapy for the Treatment of Genitourinary Syndrome of Menopause: A Protocol for Systematic Review and Meta-Analysis of Clinical Trials - Pessoa, Lisieux de Lourdes Martins Nóbrega; Sarmento, Ayane Cristine Alves; Medeiros, Kleyton Santos; Costa, Ana Paula Ferreira; Gonçalves, Ana Katherine; Cobucci, Ricardo Ney (Frontiers in Reproductive Health, 2021)
Laser therapy has been proposed to improve the symptoms of genitourinary syndrome of menopause (GSM), especially in women who do not accept hormonal therapy or are at a high risk of complications if they undergo hormonal therapy. However, studies evaluating the effectiveness and safety of laser treatment for GSM have shown controversial results. Thus, we aimed to determine the efficacy and safety of laser therapy in post-menopausal women with GSM. We have developed a protocol according to the Preferred Reporting Items for Systematic Review and Meta-analysis Protocol using the population, intervention, comparison, outcome, and study design (PICOS) framework for post-menopausal women who have received no treatment, laser therapy, placebo, or vaginal estrogen for GSM. As per our protocol, randomized controlled trials and quasi-randomized trials, regardless of language of publication, will be searched in PubMed, Embase, Scopus, Web of Science, Cochrane Central Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature, and clinicaltrials.gov. Gray literature will be searched in Open Gray and Google Scholar. The reference lists will be scanned for additional trials, and the authors will be contacted if necessary. Outcome data reported in a trial registry, even when no published results were available, will be analyzed. The search will be performed using key terms, such as “post-menopausal women,” “menopausal genitourinary syndrome,” “vulvovaginal atrophy,” and “laser therapy.” Two review authors will independently screen the titles and abstracts, while three others will independently evaluate the full text of each study to determine its eligibility for this systematic review (SR). Any disagreement will be resolved through discussion and consensus. Data extraction will be performed independently using a standardized data collection form. Clinical outcomes, including vaginal atrophy, vaginal pH, dryness, dyspareunia, itching, burning, dysuria, urinary frequency, urinary urgency, and urinary incontinence, will be systematically evaluated. We will not perform a separate search for adverse effects; instead, we will consider the adverse effects described in the included studies. Furthermore, we will summarize the effects of dichotomous outcomes as risk ratios with 95% confidence intervals. On the other hand, continuous outcomes will be summarized by expressing treatment effects as a mean difference with standard deviation or as a standardized mean difference when different scales were used to measure the same outcome. We will use the Cochrane Risk of Bias 2 tool for bias assessment and the Grading of Recommendations Assessment, Development and Evaluation approach to rate the overall certainty of evidence. Review Manager 5.3.5 will be used for quantitative data synthesis, subgroup analysis, sensitivity analysis, meta-regression, and risk of bias assessment. The SR findings will provide highly relevant evidence through the synthesis of well-designed and robust clinical trials on the effectiveness and safety of laser therapy in GSM. The Prospective Register of Systematic Reviews (PROSPERO) registration number (2021) of the SR is CRD42021253605.